Electrical stimulation of the antagonist muscle during cycling exercise interval training improves oxygen uptake and muscle strength - Hashida, R.; Takano, Y.; Matsuse, H.; Kudo, M.; Bekki, M.; Omoto, M.; Nago, T.; Kawaguchi, T.; Torimura, T.; Shiba, N. (The Journal of Strength and Conditioning Research, 2021)
A hybrid training system (HTS) is a resistance exercise method that combines voluntary concentric muscle contractions and electrically stimulated eccentric muscle contractions. We devised an exercise technique using HTS on cycle ergometer (HCE). The purpose of this study was to compare cardiorespiratory function and muscle strength when cycling exercise is combined with electrical stimulation over an extended period. Twenty-nine healthy young men were divided into an HCE group (n = 14) and a volitional cycle ergometer (VCE alone) group (n = 15). All subjects performed 30-minute cycling exercise interval training sessions 3 times a week for 6 weeks. The Vo2peak of both groups significantly increased compared with the pretraining period (HCE group: from 31.3 ± 4.4 [ml/kg/min] pretraining to 37.6 ± 6.7 [ml/kg/min] post-training [p = 0.0024] and VCE group: from 34.0 ± 7.1 [ml/kg/min] pretraining to 38.4 ± 8.2 [ml/kg/min] [p = 0.0057]). After the training, there was no significant difference of changes in Vo2peak between the HCE and the VCE groups (p = 0.7107). In the VCE group, the maximal isokinetic torque of knee extension (60°/s) post-training did not significantly increase compared with the pretraining period (VCE group: from 2.4 ± 0.5 [N·m/kg] pretraining to 2.5 ± 0.4 [N·m/kg] [p = 0.4543]). By contrast, in the HCE group, the maximal isokinetic torque of knee extension (60°·s-1) post-training significantly increased compared with pretraining period (HCE group: from 2.5 ± 0.3 [N·m/kg] pretraining to 2.8 ± 0.3 [N·m/kg] [p < 0.0001]). The change in knee extension torque was significantly greater for the HCE group than for the VCE group (p = 0.0307). In conclusion, cardiopulmonary function and knee extension strength were improved by the use of HCE.